Premalignant cervicofacial lesions and nonmelanoma skin cancer in elderly patient - Yudit Algozain Acosta; Eliseo Capote Leyva; Maritza Ivis Hechavarría Suclar; Salvador Roberto Mora González; Juan Carlos Quintana Díaz; Idalberto Arencibia Galán (Editorial Ciencias Médicas, 2015)
Introduction: aging is currently the main demographic problem for Cuban population. The frequency of skin cancer and other premalignant lesions in this protective organ has increased in recent years, especially in elderly patients. Objective: to determine clinical and epidemiological behavior of the aforementioned lesions in elderly patients. Method: an observational and descriptive cross-sectional study was conducted in 2011, between March and November, with patients from the area of the "Adrian Sansaric" polyclinic in the municipality of Artemisa. A sample of 100 patients showing premalignant and/or malignant lesions in the cervicofacial region was selected from an initial population of 481 elderly patients. Results: the most frequent premalignant and malignant lesions were senile keratosis (95%) and the basal cell carcinoma (12 %), respectively. Skin colour, age, sun exposure and occupational risk were the main factors associated with these lesions. Patients aged 80 or more, with white skin, increased sun exposure and occupational risk were the most susceptible. Premalignant lesions were located in the genian (75 %) and frontal (62.5 %) regions while the malignant lesions were more frequent in the nasal region (50 %). Conclusions: premalignant and malignant lesions in the skin show a high prevalence among elderly patients which significantly threaten their longevity and aesthetics.